Scleral Ischemia in Acute Ocular Chemical Injury: Long-Term Impact on Rehabilitation With Limbal Stem Cell Therapy. Issue 2 (February 2019) - Gupta, Nidhi; Singh, Aastha; Mathur, Umang
Abstract : Purpose: This study describes the impact of scleral ischemia on globe survival in cases of acute chemical injury and the outcome of limbal stem cell transplant in these eyes. Methods: This is a single-center, retrospective case study that reviews outcomes in all patients with acute chemical injury of grades IV and above who presented within 6 weeks from injury. The period of the study is between May 2012 and May 2017. Eyes presenting without scleral ischemia underwent amniotic membrane transplantation (group A), whereas eyes presenting with scleral ischemia underwent tenonplasty with amniotic membrane transplantation (group B). Simple limbal epithelial transplantation (SLET) was performed at 6 months in all consenting patients from both these groups. The primary outcome was defined as globe preservation at 3 months, whereas the secondary outcome was defined as SLET success at 1 year. Results: Twenty-three eyes of the 23 patients were included in our study. Of the 13 eyes in group B, 2 eyes developed phthisis and 2 eyes developed hypotony. None of the 10 eyes in group A developed hypotony or phthisis. The eyes that developed into hypotony and phthisis had presented with more extensive scleral ischemia (>180 degrees). In group B, 5 of 7 patients failed SLET. This was high compared with group A in which 2 of 8 patients failed SLET. Conclusions: The presence and extent of scleral ischemia are important prognostic factors when assessing recovery in eyes with acute chemical injury. The authors recommend that it be added as a poor prognostic indicator in the existing classifications of acute chemical injury.